Bone Marrow Mesenchymal Stem Cells Regulate Coagulation and Inflammation Together in Methotrexate Induced Lung Injury Rat Model - Haggag,Nawal Zakaria (2019)
Abstract Clinical research has shed the light on the relation between coagulation and inflammation. Coagulation cascade is activated in lung injury resulting in thrombotic and fibrotic lesions. Such a cascade is initiated by inflammation, then the two systems intense each other. New therapies that modulate coagulation and inflammation will be more successful than therapies targeting only one of them. Mesenchymal stem cells showed anti-inflammatory functions in animal models. The role of mesenchymal stem cells in methotrexate induced lung injury model was evaluated, but no studies scoped on the role of stem cells in coagulation associated with inflammation in such models. This study focuses on the therapeutic role of mesenchymal stem cells against the development of clotting in methotrexate induced lung injury rat model. Results showed that mesenchymal stem cells treatment for 4 weeks caused a decrease in lung activated coagulation factors; protease activated receptor-1, fibrinogen, plasminogen activator inhibitor-1 and platelet count with a decrease in inflammatory factors; tumor necrosis factor-α, interferon- γ, interleukin-8, monocyte chemoattractant protein-1 and total leukocyte count. Thus, mesenchymal stem cells have anti-inflammatory potency against clotting risk in methotrexate induced lung injury model. This opens the outlook for stem cells as a new therapy that moderates coagulation associated with inflammation.